An assessment of sociodemographic factors and family planning practices in Jamnagar, Gujarat, India: a cross sectional study - Rathod, Mittal; Parmar, Dipesh; Gohel, Aniruddha; Kaliya, Mehul; Unadakat, Sumit; Patel, Nirmika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: India was the first country in the world to launch a National Family Planning Programme in 1952. It was purely a demographic programme with the sole objective of reducing the birth rate to stabilize the population. As per 2011 census population increased with the growth rate of 17.7%. Thus even after 63 years of programme & many more new advances & updates in programme, India could not reach its target of at least 60% of couple protection rate. So there would be some definite factors prohibiting its use. Methods: A cross section study of 450 reproductive age group women was conducted to find out the factors of unmet need of contraception & socio demographic profile. Results: In present study couple protection rate was 57.11%, majority being permanent sterilization. The selection of contraception was influenced by her husband in 43.24% & by mother-in-law in 62.16%. Conclusions: The study revealed that almost half of the couple population was using the contraception that included temporary as well as permanent methods of contraception.